2021
DOI: 10.1002/lary.29580
|View full text |Cite
|
Sign up to set email alerts
|

Paper Patching Versus Watchful Waiting of Traumatic Tympanic Membrane Perforations: A Meta‐Analysis

Abstract: Objectives/Hypothesis The aim of the study was to investigate the healing rates, the restoration of hearing, and the time for complete healing of paper patching versus watchful waiting for traumatic tympanic membrane perforations (TTMPs). Study Design Systematic review with meta analysis. Methods Publications were selected by a search on “PubMed,” “Embase,” and “Web of Science.” A meta‐analysis of risk ratios for paper patching (intervention arm) and watchful waiting (control arm) was performed. Results Five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Third, recent studies including meta-analysis showed that the recovery rate of TTMP in the paper patching group was statistically higher than that in the observation group. 22 , 23 Therefore, it may lower the necessity of future surgical treatment for tympanic membrane perforation compared to the watchful observation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent studies including meta-analysis showed that the recovery rate of TTMP in the paper patching group was statistically higher than that in the observation group. 22 , 23 Therefore, it may lower the necessity of future surgical treatment for tympanic membrane perforation compared to the watchful observation.…”
Section: Discussionmentioning
confidence: 99%
“…After the enrolment process was completed, a manual review of all the references cited in the enrolled studies was performed in search of additional articles for inclusion. This process was performed to allow studies that had not been identified according to our keyword search to be identified and assessed for suitability for inclusion; this method having been demonstrated as being efficient for additional article inclusion in otolaryngology (20)(21)(22). A quantitative data sheet was constructed, and each relevant publication was analyzed in terms of demographic data and affected cranial and spinal nerves.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%